Metode Steganografi EOF untuk Penyisipan Pesan Teks Tersembunyi - Malau, Mega; Hutahaean, Sarah; Siboro, Gilberd (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2025)
The transmission of information has become an essential aspect of human life in the modern technological era. Innovations continue to be developed to simplify and accelerate data exchange processes. However, threats to information security, such as data theft, sabotage, and unauthorized access, have also increased significantly. Therefore, innovative solutions are needed to protect information, especially confidential data involving two parties who wish to maintain its secrecy. In this context, research on steganography has become highly relevant. This study employs the End Of File (EOF) steganography technique, which enables embedding secret messages at the end of digital image files. This technique is chosen for its ability to conceal data without significantly altering the main structure of the image file. The embedding process is carried out meticulously so that the final product, known as the stego image, resembles an ordinary image file without any noticeable signs of modification. The primary advantage of the EOF technique lies in its efficiency in embedding and retrieving secret messages, making it a suitable solution for secure message transmission. The findings indicate that stego images produced using the EOF technique not only preserve the integrity of the original image but also enable quick and easy retrieval of messages by authorized recipients. This makes the technique an effective method to prevent data theft or sabotage during transmission. Amid the growing threats of cybercrime, EOF steganography offers an innovative solution to ensure information security while maintaining message confidentiality. Thus, it serves as a promising alternative for advancing future information security technologies.